Sliding member
The stainless steel alloy sliding member with a matrix, hard, and intermediate hard phases addresses wear issues by minimizing hard phase dropout, improving wear resistance in high-temperature conditions.
Patent Information
- Application Number
- JP2021050016
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-03-24
AI Technical Summary
Conventional sliding members face issues with wear progression due to high matrix content leading to material holding and increased friction, or excessive hard phase content causing aggression to the opponent material, with the hard phase dropout exacerbating wear.
A stainless steel alloy sliding member with a matrix phase, larger hard phase, and intermediate hard phase, where the hard phase is surrounded by the intermediate phase, reducing dropout and maintaining wear resistance.
The solution effectively reduces hard phase dropout and wear by retaining the hard phase within the intermediate phase, enhancing wear resistance in high-temperature environments.
Smart Images

Figure 0007623177000001 
Figure 0007623177000002 
Figure 0007623177000003
Abstract
Description
[Technical field]
[0001] This embodiment relates to a sliding member formed of a stainless steel alloy. [Background technology]
[0002] Rotating bodies used for exhaust gas after combustion, such as exhaust turbines, are exposed to high-temperature environments. Therefore, sliding members used in bearings that support the rotating bodies are required to have high heat resistance. In addition, the sliding members are required to have high wear resistance even in high-temperature environments. Patent Document 1 discloses an iron-based sintered alloy that contains a Co alloy phase as a hard phase.
[0003] However, in the case of conventional sliding members, the ratio of the matrix in the sliding member is high, and the matrix is likely to adhere to the sliding counter material in a high-temperature environment. Therefore, there is a problem that the wear of the sliding member due to adhesion is likely to progress. On the other hand, if the ratio of the hard phase in the sliding member is increased, the adhesion to the counter material is reduced, but the aggressiveness of the sliding member against the counter material increases. Therefore, there is a problem that the wear of the counter material progresses. In particular, when the fine hard phase increases, the hard phase is likely to fall off from the matrix, and the fallen hard phase acts as an abrasive. Therefore, there is a problem that the friction coefficient increases, and as a result, the wear of both the sliding member and the counter material is likely to progress. In addition, if the hard phase is increased to reduce the fall-off of the hard phase, there is a problem that the aggressiveness to the counter material increases, and as a result, the wear of the counter material is likely to progress. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 2-270943 Summary of the Invention [Problem to be solved by the invention]
[0005] Therefore, an object of the present invention is to provide a sliding member which reduces the detachment of the hard phase and has high wear resistance even in a high-temperature environment. [Means for solving the problem]
[0006] In order to solve the above problems, the slide member of the present embodiment is made of a stainless steel alloy and includes a matrix phase, a hard phase, and an intermediate hard phase. The hard phase has a harder property than the matrix phase and is dispersed in the matrix phase. The intermediate hardness phase has a hardness between that of the matrix phase and the hard phase. The hard phase is surrounded by the intermediate hard phase.
[0007] In this way, the sliding member of this embodiment has an intermediate hard phase. The hard phase is surrounded by the intermediate hard phase. Therefore, the hard phase does not exist alone, but is surrounded by the intermediate hard phase. As a result, the hard phase is held in the intermediate hard phase, which has a hardness closer to that of the matrix phase, and is less likely to fall off even when it is refined. As a result, the hard phase is less likely to fall off, and wear of the sliding member and the mating material caused by the fallen hard phase is reduced. In addition, since the hard phase is less likely to fall off, the amount of wear is reduced while maintaining the proportion of the hard phase. Therefore, wear resistance can be improved even in high-temperature environments. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a structure of a sliding member according to an embodiment; [Diagram 2] FIG. 1 is a schematic diagram showing the composition of materials constituting a sliding member according to one embodiment. [Diagram 3] FIG. 1 is a schematic diagram showing test conditions for a sliding member according to an embodiment; [Figure 4] FIG. 1 is a schematic diagram showing test results of examples and comparative examples of a sliding member according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, a sliding member according to an embodiment will be described in detail with reference to the drawings. As shown in FIG. 1, the sliding member 10 includes a matrix phase 11, a hard phase 12, and an intermediate hard phase 13. The sliding member 10 is formed of a stainless steel alloy. The sliding member 10 is formed of stainless steel, such as SUS316, which contains Cr. The matrix phase 11 is a main part of the structure of the stainless steel that forms the sliding member 10, and contains a hard phase 12 and an intermediate hard phase 13 in the structure. FIG. 1 corresponds to a cross section of the sliding member 10 cut along an arbitrary plane. In this case, the cross section can be set arbitrarily, such as in the plate thickness direction of the sliding member 10, perpendicular to the plate thickness direction, or inclined therefrom.
[0010] The hard phase 12 has a higher hardness than the matrix phase 11 and is dispersed in the matrix phase 11. The hard phase 12 is formed of a compound of metal elements that constitute the stainless steel. The intermediate hard phase 13 has a hardness between the matrix phase 11 and the hard phase 12. That is, the intermediate hard phase 13 has a higher hardness than the matrix phase 11, but a lower hardness than the hard phase 12. When SUS316 is used as the stainless steel, for example, the hard phase 12 is a (Cr,Fe)3C2 compound, and the intermediate hard phase 13 is a (Cr,Fe)7C3 compound.
[0011] The hard phase 12 dispersed in the matrix phase 11 is surrounded by the intermediate hard phase 13. That is, the hard phase 12 does not precipitate independently in the matrix phase 11, but precipitates in the matrix phase 11 while being surrounded by the intermediate hard phase 13. On the other hand, the intermediate hard phase 13 includes a phase that precipitates independently in the matrix phase 11 without surrounding the hard phase 12. That is, the sliding member 10 of this embodiment includes both an intermediate hard phase 13 that includes the hard phase 12 in its structure and an intermediate hard phase 13 that does not include the hard phase 12 in its structure. In FIG. 1, only a part of the hard phase 12 is indicated by a reference symbol for simplicity. The particles surrounded by the intermediate hard phase 13 are the hard phase 12.
[0012] The hard phase 12 has a higher hardness than the matrix phase 11. Therefore, when the hard phase 12 is finely divided and dispersed in the matrix phase 11, it is likely to fall off from the matrix phase 11, which has a large difference in hardness. In other words, when the particle size of the hard phase 12 is reduced, it is likely to fall off from the matrix phase 11, which has a large difference in hardness. The fallen particles of the hard phase 12 act similarly to an abrasive in the sliding portion between the counter member and the sliding member 10, and cause the wear of the counter member and the sliding member 10 to progress.
[0013] On the other hand, when the particle size of the hard phase 12 is increased, it is difficult for the hard phase 12 to fall off from the matrix phase 11, but since the hardness is high, it is easy to damage the mating material, leading to the progress of wear of the mating member. For these reasons, it is required to prevent the hard phase 12 from falling off from the matrix phase 11 while making it finer. In the case of this embodiment, the intermediate hard phase 13 has a hardness between the matrix phase 11 and the hard phase 12 as described above. As a result, the hard phase 12 is held by the intermediate hard phase 13, which has a smaller difference in hardness compared to the matrix phase 11, and falling off is reduced. In this way, the sliding member 10 of this embodiment includes the intermediate hard phase 13 having a hardness between the matrix phase 11 and the hard phase 12, and by surrounding the hard phase 12 with the intermediate hard phase 13, it is possible to reduce the falling off of the hard phase 12 from the matrix phase 11 while making the hard phase 12 finer.
[0014] The sliding member 10 has an area ratio of the intermediate hard phase 13 set to 10 to 50%. That is, when an arbitrary observation field is set for the sliding member 10 and the observation field is observed, the intermediate hard phase 13 is contained in the observation field at an area ratio of 10 to 50%. The area ratio of the intermediate hard phase 13 is more preferably 20 to 40%. If the area ratio of the intermediate hard phase 13 is less than 10%, the ability of the intermediate hard phase 13 to hold the hard phase 12 becomes insufficient. In addition, the intermediate hard phase 13 has a higher hardness than the matrix phase 11. Therefore, if the area ratio of the intermediate hard phase 13 contained in the entire sliding member 10 exceeds 50%, the sliding member 10 becomes brittle due to the intermediate hard phase 13 having a high hardness. Therefore, the area ratio of the intermediate hard phase 13 in an arbitrary observation field is preferably 10 to 50%.
[0015] The equivalent circle diameter of the intermediate hard phase 13 is set to 10 to 100 μm on average. The equivalent circle diameter of the intermediate hard phase 13 is preferably 20 to 80 μm, and more preferably 30 to 60 μm. If the equivalent circle diameter of the intermediate hard phase 13 is less than 10 μm, the particles become too small, making it difficult to include the hard phase 12 in the structure of the intermediate hard phase 13. On the other hand, if the equivalent circle diameter of the intermediate hard phase 13 exceeds 100 μm, the particles of the intermediate hard phase 13 in the matrix phase 11 become too large, making the sliding member 10 brittle. Therefore, the equivalent circle diameter of the intermediate hard phase 13 is preferably 10 to 100 μm on average.
[0016] The circle-equivalent diameter of the hard phase 12 is set to 0.5 μm to 10 μm on average. The circle-equivalent diameter of the hard phase 12 is preferably 1.0 to 8.0 μm. If the circle-equivalent diameter of the hard phase 12 is less than 0.5 μm, the particles become too small, and the wear resistance required of the hard phase 12 is not exhibited. On the other hand, if the circle-equivalent diameter of the hard phase 12 exceeds 10 μm, the aggressiveness of the hard phase 12 becomes too high, leading to wear of the mating member. Therefore, the circle-equivalent diameter of the hard phase 12 is preferably 0.5 μm to 10 μm on average.
[0017] The hard phase 12 is contained in an average of 1 to 20 pieces in an arbitrary observation field set to 100 μm × 100 μm. The number of hard phases 12 contained in this observation field is preferably 2 to 10 pieces, and more preferably 3 to 5 pieces. If the number of hard phases 12 in the observation field is less than 1, it goes without saying that the wear resistance required of the hard phase 12 is not exhibited. On the other hand, it is difficult to manufacture a hard phase having more than 20 hard phases 12 in the observation field. Therefore, it is preferable that the hard phase 12 is contained in an average of 1 to 20 pieces in a given observation field.
[0018] Next, a method for manufacturing the sliding member 10 having the above configuration will be described. In this embodiment, a mixed powder is obtained by mixing SUS316L powder, powder A, and powder B. Zinc stearate is added to the obtained mixed powder as an additive to prevent seizure during molding. Each of the SUS316L, powder A, and powder B contains each element as shown in FIG. 2. The composition of each element contained in the obtained example is set by adjusting the mixing ratio of each of these powders.
[0019] The mixed powder with additives was filled into a cylindrical mold and compressed at 7 t / cm 2 The molded compact is molded by applying a force of about 1000°C to about 1200°C in a sintering furnace. The molded compact is heated and sintered at about 1100°C to 1200°C. In this way, the molded compact of the slide member 10 of this embodiment is obtained. In this case, in the slide member 10 of this embodiment, the generation of the hard phase 12 and the intermediate hard phase 13 precipitated in the matrix phase 11 is controlled by the mixing ratio of each powder material, that is, the composition of each element. Therefore, the obtained molded compact does not require heat treatment such as annealing or quenching. For example, if there is a shortage of C as an added element, the hard phase 12 does not precipitate in the matrix phase 11. Also, if there is a shortage of Cr as an added element, the intermediate hard phase 13 does not precipitate in the matrix phase 11.
[0020] The content and function of each element contained in the sliding member 10 will be described with reference to the origin of each powder. The Cr content is 21.5 to 28.4 mass%, and preferably 23.0 to 27.0 mass%. Cr contributes to improving corrosion resistance and fracture toughness. If the Cr content is too high, the strength of the slide member 10 is likely to decrease in a high-temperature environment.
[0021] The content of Ni is 7.9 to 15.0 mass%, and preferably 8.5 to 11.8 mass%. Ni contributes to improving corrosion resistance and impact resistance. Since Ni is expensive, it is preferable to reduce the content as much as possible within the range that contributes to improving corrosion resistance and impact resistance. The content of Mo is 0.5 to 4.0 mass %, and preferably 1.0 to 3.0 mass %. Mo contributes to improving strength and corrosion resistance in high-temperature environments. If the content of Mo is too high, the fracture toughness of the slide member 10 is likely to decrease.
[0022] The content of C is 1.0 to 2.2 mass %, and preferably 1.2 to 2.0 mass %. C contributes to the formation of carbides that become a hard phase. If the content of C is too high, the fracture toughness of the slide member 10 is likely to decrease. The content of Si is 0 to 1.0 mass %. Although the addition of Si is not essential, it is added for deoxidation during the production stage of each powder. If the content of Si is too high, the strength and toughness of the slide member 10 are likely to decrease.
[0023] The content of P is 0.4 to 1.5 mass %, and preferably 0.6 to 1.3 mass %. P contributes to improving sinterability. If the content of P is too high, the corrosion resistance of the slide member 10 is likely to decrease. S is an unavoidable impurity. The content of Mn is 0 to 2.0 mass %. Although the addition of Mn is not essential, it contributes to improving strength. If the content of Mn is too high, the toughness of the slide member 10 is likely to decrease.
[0024] (Example) Examples and comparative examples of this embodiment will be described below. The test pieces of the examples and comparative examples were subjected to a sliding test under the conditions shown in Fig. 3, and the wear resistance was evaluated based on the amount of wear. The sliding test was performed in a high temperature environment of 750°C, and a load of 3N was applied. The test piece was slid between the test piece and the mating member at 10 Hz over a distance of 0.5 mm for 15 minutes. The test piece was in the shape of a flat plate. The mating member that slid against the test piece was in the shape of a sphere with a radius of 5 mm, and was made of SUS316L.
[0025] All of Example 1 to Example 23 have a hard phase 12 surrounded by an intermediate hard phase 13. In contrast, Comparative Example 1 does not contain a hard phase 12, and Comparative Example 2 does not contain an intermediate hard phase 13. Thus, Comparative Example 1, which does not contain a hard phase 12, lacks strength in a high-temperature environment, and the action of the hard phase 12 cannot be expected, resulting in an increase in wear. On the other hand, Comparative Example 2, which does not contain an intermediate hard phase 13, invites the hard phase 12 to fall off during sliding, resulting in an increase in wear. Therefore, it can be seen that Examples 1 to 23, which contain a hard phase 12 surrounded by an intermediate hard phase 13, have improved strength in a high-temperature environment, prevent the hard phase 12 from falling off, and improve wear resistance.
[0026] In all of Examples 1 to 13, the area ratio of the intermediate hard phase 13 is 10 to 50%. In addition, in Examples 1 to 13, the intermediate hard phase 13 has a circle equivalent diameter of 10 to 100 μm, the hard phase 12 has a circle equivalent diameter of 0.5 to 10 μm, and 1 to 20 hard phases 12 are contained in an arbitrary observation field set to 100 μm × 100 μm. It is understood that Examples 1 to 13, which satisfy these conditions, have significantly improved wear resistance in high-temperature environments.
[0027] In contrast, although Examples 14 and 15 have a hard phase 12 surrounded by an intermediate hard phase 13, the area ratio of the intermediate hard phase 13, the circle equivalent diameter of the intermediate hard phase 13, the area ratio of the hard phase 12, and the circle equivalent diameter of the hard phase 12 are outside the above conditions. Therefore, Examples 14 and 15 have improved wear resistance in a high temperature environment compared to Comparative Examples 1 and 2, but are inferior to Examples 1 to 13.
[0028] Similarly, in Examples 16 and 17, the area ratio of the intermediate hard phase 13 does not satisfy the conditions. In Examples 18 and 19, the equivalent circle diameter and area ratio of the intermediate hard phase 13 do not satisfy the conditions. In Examples 20 and 21, the equivalent circle diameter of the hard phase 12 does not satisfy the conditions. In Examples 22 and 23, the equivalent circle diameter and number of the hard phases 12 do not satisfy the conditions. This shows that Examples 1 to 13, which satisfy all of the above conditions, i.e., the area ratio of the intermediate hard phase 13, the equivalent circle diameter of the intermediate hard phase 13, the equivalent circle diameter of the hard phase 12, or the number of the hard phases 12, have improved seizure resistance compared to Examples 14 to 23, which do not satisfy even one of these conditions.
[0029] The present invention described above is not limited to the above-described embodiment, and can be applied to various embodiments without departing from the gist of the invention. [Explanation of symbols]
[0030] In the drawing, 10 denotes a sliding member, 11 denotes a matrix phase, 12 denotes a hard phase, and 13 denotes an intermediate hard phase.
Claims
1. 21.5 to 28.4 mass% Cr; 7.9 to 15.0 mass% Ni; 0.5 to 4.0 mass% Mo; 1.0 to 2.2 mass% C; 0 to 1.0 mass% Si; 0.4 to 1.5 mass% P; 0 to 2.0 mass% Mn; and the balance being Fe containing unavoidable impurities, A matrix phase of the alloy; a hard phase having a hardness greater than that of the matrix phase and dispersed in the matrix phase; an intermediate hard phase having a hardness between that of the matrix phase and that of the hard phase; The hard phase is surrounded by the intermediate hard phase, The intermediate hard phase has an equivalent circle diameter of 10 to 100 μm.
2. 2. The slide member according to claim 1, wherein the intermediate hard phase occupies an area ratio of 10 to 50% in any observation field.
3. The sliding member according to claim 1, wherein the hard phase has an equivalent circle diameter of 0.5 to 10 μm.
4. A sliding member according to claim 3, wherein the hard phase is contained in an arbitrary observation field set to 100 μm x 100 μm in an amount of 1 to 20 pieces.
5. The hard phase is a (Cr,Fe)3C2 compound, The slide member according to claim 1 , wherein the intermediate hard phase is a (Cr,Fe) 7 C 3 compound.
Citation Information
Patent Citations
Sintered alloy for bearing withstanding high temperature and its production
JP1990270943A
Sintered valve seat and production method therefor
JP2007023383A
Sintered valve seat and method for producing the same
JP2007113101A
Wear resistant sintered alloy and its production method
JP2007238987A
Sintered alloy and manufacturing method thereof
JP2013057094A